2018
DOI: 10.1111/bjdp.12231
|View full text |Cite
|
Sign up to set email alerts
|

My mind, your mind, and God's mind: How children and adults conceive of different agents’ moral beliefs

Abstract: Extending prior research on belief attributions, we investigated the extent to which 5- to 8-year-olds and adults distinguish their beliefs and other humans' beliefs from God's beliefs. In Study 1, children reported that all agents held the same beliefs, whereas adults drew greater distinctions among agents. For example, adults reported that God was less likely than humans to view behaviors as morally acceptable. Study 2 additionally investigated attributions of beliefs about controversial behaviours (e.g., te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Presenting germs as something “bad” may negate indicators of the ways in which germs are like us (e.g., being alive, animate). On the other hand, one motive for the development of a concept of God is to form a personal relationship with God (Mahoney, 2013); as such, cuing children to see God as animate and intrinsically “good” may facilitate children's emotional investment in engaging with thoughts of God (Boyer, 2003; Gray & Wegner, 2010; Heiphetz, Lane, Waytz, & Young, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Presenting germs as something “bad” may negate indicators of the ways in which germs are like us (e.g., being alive, animate). On the other hand, one motive for the development of a concept of God is to form a personal relationship with God (Mahoney, 2013); as such, cuing children to see God as animate and intrinsically “good” may facilitate children's emotional investment in engaging with thoughts of God (Boyer, 2003; Gray & Wegner, 2010; Heiphetz, Lane, Waytz, & Young, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As described above, one project asked how 3-to 12-year-olds attribute knowledge of diverse information, including knowledge regarding past behaviors, to a fictional person described as omniscient . Another series of studies showed that 5-to 8-yearolds attribute similar moral beliefs (e.g., that it is not okay to hit) to themselves, other humans, and God (Heiphetz, Lane, Waytz, & Young, 2018). However, this work did not ask participants to attribute moral knowledge to God (e.g., whether God knows when people hit each other).…”
Section: The Role Of Theory Of Mind and Wishful Thinking In Children's Moralizing Concepts Of The Abrahamic Godmentioning
confidence: 95%
“…In other words, children who are certain that God knows their actions may perform more of the kinds of behaviors that God MORALIZING GOD CONCEPTS ostensibly prefers. Because United States culture typically portrays God as wanting people to perform pro-social behaviors (Evans, 2013;Hare, 2007;Heiphetz et al, 2018), attributing greater moral knowledge to God may predict greater pro-sociality.…”
Section: Studymentioning
confidence: 99%
“…Thus, Bar ett and co lea ues claimed, when the fo k likewise attribute these human-like limitations to these supernatural agents, they are providing an anthropomorphized, theologica ly incor ect representation. This view of anthropomorphism toward supernatural agent concepts has been widely influential in CSR as it has sur eptitiously ap eared and been adopted in much subsequent research (Bar ett, 2012; Bar ett and Richert, 2003;Bar ett et al, 2001;Heiphetz et al, 2016;Heiphetz et al, 2018;Knight et al, 2004;Lane et al, 2010;Shtulman, 2008;Shtulman and Lindeman, 2016;Slone, 2007). This is largely because CSR researchers have retained a near laser focus on the Judeo-Christian-Islamic God to the neglect of a l others.…”
Section: Anthropomorphism Qua Human-like Limitationsmentioning
confidence: 99%